Engineering thermodynamics and fluid mechanics - Bhattacharyya, Basudeb (New Age International (P) Ltd, 2012)
Engineering thermodynamics and fluid mechanics / Bhattacharyya, Basudeb. -- Kolkata: New Age International (P) Ltd, 2012 536.7 B575 No. of Copies : 2